Interlayer adhesive, interlayer adhesive for touch panel and touch panel
By using a polyvinyl acetal resin resin layer containing phosphate in the interlayer adhesive of the touch panel, the problem that the touch panel is prone to whitening under high temperature and high humidity conditions is solved, and the effect of effectively suppressing whitening and improving visibility is achieved.
Patent Information
- Application Number
- CN202380057949.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-08
- Filing Date
- 2023-08-07
- Publication Date
- 2025-03-18
AI Technical Summary
Under the working conditions of the touch panel, especially when the temperature and humidity are high, when polyvinyl acetal resin is used as the interlayer adhesive, it is easy to whiten the peripheral portion of the touch panel, resulting in a decrease in visibility.
A resin layer composed of polyvinyl acetal resin is used. The resin layer contains a phosphate ester, the concentration of the phosphate ester is 0.1 mass % or more, the HLB is 10 or less, and a polyoxyalkylene alkyl ether group is used as an interlayer adhesive to inhibit whitening.
通过使用含有磷酸酯的层间粘接剂,能够有效抑制触摸面板周缘部的白化,提高可视性。
Smart Images

Figure BDA0005262014950000021 
Figure BDA0005262014950000022 
Figure BDA0005262014950000031
Abstract
Description
Technical Field
[0001] The present invention relates to an interlayer adhesive, an interlayer adhesive for a touch panel, and a touch panel. Background Art
[0002] In recent years, touch panels that allow information to be input by touching with a finger are sometimes provided in portable information terminals such as smartphones and tablet computers, and in-vehicle displays.
[0003] The touch panel has a multi-layer structure using cover glass, sensor glass, liquid crystal panel and other components. In addition, the transparency, brightness, contrast and other aspects of the display screen are improved by filling the gaps between the components with fillers to enhance visibility.
[0004] For example, Patent Document 1 discloses an invention relating to an interlayer filling material for a touch panel, wherein the interlayer filling material for a touch panel is characterized in that it contains polyvinyl acetal, a reactive diluent, and a photopolymerization initiator, and records that a touch panel laminate having excellent followability to height differences and being less prone to cracking and breakage can be obtained.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2016 / 186029 Summary of the invention
[0008] Problems to be solved by the invention
[0009] When polyvinyl acetal resin is used as a material for bonding between layers of a touch panel as described in Patent Document 1, the impact absorption is improved and cracking and breakage are not easy to occur. However, according to the research of the inventors of this application, when polyvinyl acetal resin is used as an interlayer adhesive of a touch panel with a sensor glass, whitening is easily generated at the peripheral portion of the touch panel under the operating conditions of the touch panel (when voltage is applied), especially when the temperature and humidity are high. If whitening occurs, the visibility of the touch panel is reduced, so it needs to be improved.
[0010] Therefore, an object of the present invention is to provide an interlayer adhesive containing a polyvinyl acetal resin and capable of suppressing whitening, and a touch panel including the interlayer adhesive.
[0011] Means for solving problems
[0012] As a result of intensive studies, the inventors of the present application have found that the above-mentioned problems can be solved by an interlayer adhesive composed of a resin layer containing a polyvinyl acetal resin and containing a phosphate ester, thereby completing the present invention.
[0013] The gist of the present invention is as follows.
[0014] [1] An interlayer adhesive comprising a resin layer composed of a polyvinyl acetal resin, wherein the resin layer contains a phosphoric acid ester.
[0015] [2] The interlayer adhesive according to [1] above, wherein the concentration of the phosphoric acid ester in the resin layer is 0.1% by mass or more.
[0016] [3] The interlayer adhesive according to [2] above, wherein the concentration of the phosphoric acid ester in the resin layer is 0.5 mass % or less.
[0017] [4] The interlayer adhesive according to any one of [1] to [3] above, wherein the phosphate ester has an HLB of 10 or less.
[0018] [5] The interlayer adhesive according to any one of [1] to [4] above, wherein the phosphoric acid ester has a polyoxyalkylene alkyl ether group.
[0019] [6] The interlayer adhesive according to [5] above, wherein the polyoxyalkylene alkyl ether group is a compound represented by formula (1).
[0020]
[0021] (R1 is an alkyl group having 8 to 18 carbon atoms, R2 is an alkylene group having 2 to 6 carbon atoms, n is 1 to 10, and * represents a connecting bond)
[0022] [7] The interlayer adhesive according to any one of [1] to [6] above, wherein the phosphate ester is a compound represented by formula (2) or formula (3).
[0023]
[0024] (R1 is an alkyl group having 8 to 18 carbon atoms, and n is 1 to 10)
[0025] [8] The interlayer adhesive according to any one of [1] to [7] above, wherein the phosphate ester has a dodecyl group.
[0026] [9] The interlayer adhesive according to any one of [1] to [8] above, wherein the polyvinyl acetal resin is a polyvinyl butyral resin.
[0027]
[10] The interlayer adhesive according to any one of [1] to [9] above, wherein the resin layer contains a plasticizer.
[0028]
[11] An interlayer adhesive for a touch panel, comprising the interlayer adhesive according to any one of [1] to
[10] above.
[0029]
[12] A touch panel comprising the interlayer adhesive according to any one of [1] to
[10] above.
[0030] Effects of the Invention
[0031] According to the present invention, there can be provided an interlayer adhesive including a polyvinyl acetal resin and capable of suppressing whitening, and a touch panel including the interlayer adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] [ Figure 1 ] is a schematic cross-sectional view showing one embodiment of the touch panel of the present invention.
[0033] [ Figure 2 ] is a schematic cross-sectional view showing another embodiment of the touch panel of the present invention.
[0034] <Interlayer Adhesive>
[0035] The interlayer adhesive of the present invention is composed of a resin layer containing a polyvinyl acetal resin, and the resin layer contains a phosphoric acid ester.
[0036] [Phosphate ester]
[0037] The resin layer of the present invention contains a phosphate ester. By making the resin layer contain a phosphate ester, whitening of the peripheral portion can be suppressed when used for bonding of a touch panel. Although the reason is unclear, it is believed that the inclusion of a phosphate ester can effectively suppress the aggregation of water that causes whitening.
[0038] Phosphate esters are compounds having a phosphate structure such as phosphate monoesters, phosphate diesters, and phosphate triesters, wherein all or part of the three hydrogen atoms in phosphoric acid (O=P(OH)3) are replaced by organic groups. Among them, compounds having a hydrophilic part and a lipophilic part and having the function of a surfactant are preferred, and phosphate monoesters and phosphate diesters are preferred.
[0039] From the viewpoint of further suppressing whitening, the HLB (Hydrophilic-Lipophilic Balance) of the phosphoric acid ester in the present invention is preferably 13 or less, more preferably 11 or less, further preferably 10 or less, and is preferably 4 or more, more preferably 6 or more.
[0040] It should be noted that the "HLB" in the present invention can be calculated by the Griffin method [HLB=20×(MW / MO), MW: the sum of the formula weights of the hydrophilic part, MO: molecular weight].
[0041] From the viewpoint of making the HLB to a desired value and more effectively suppressing whitening, the phosphoric acid ester in the present invention preferably has a polyoxyalkylene alkyl ether group, and more specifically, is preferably a compound having a polyoxyalkylene alkyl ether group and a phosphoric acid skeleton.
[0042] The polyoxyalkylene alkyl ether group is a group in which a polyoxyalkylene group and an alkyl group are linked via an ether bond (—O—), and has a structure represented by the formula (1).
[0043]
[0044] (R1 is an alkyl group, R2 is an alkylene group, n is 1 to 50, and * represents a connecting bond)
[0045] R1 is preferably an alkyl group having 6 to 20 carbon atoms, more preferably an alkyl group having 8 to 18 carbon atoms, and still more preferably an alkyl group having 10 to 14 carbon atoms. R1 may be a linear alkyl group or a branched alkyl group, but is preferably a linear alkyl group from the viewpoint of further suppressing whitening.
[0046] R1 can include, for example, hexyl, isohexyl, heptyl, isoheptyl, octyl, 2-ethylhexyl, isooctyl, nonyl, isononyl, decyl, isodecyl, undecyl, isoundecyl, dodecyl, isododecyl, tridecyl, isotridecyl, tetradecyl, isotetradecyl, pentadecyl, isopentadecyl, hexadecyl, isohexadecyl, 2-hexyldecyl, heptadecyl, isoheptadecyl, octadecyl, isooctadecyl, 2-octyldecyl, 2-hexyldodecyl, nonadecyl, isononadecyl, eicosyl, isoeicosyl and the like.
[0047] Among them, R1 is preferably dodecyl or isotridecyl, and more preferably dodecyl. That is, as the phosphate ester, from the viewpoint of adjusting the HLB to the desired range and further suppressing whitening, the phosphate ester having dodecyl or isotridecyl is preferred, and the phosphate ester having dodecyl is more preferred.
[0048] In the above formula (1), R2 is an alkylene group, preferably an alkylene group having 2 to 6 carbon atoms, more preferably an alkylene group having 2 to 3 carbon atoms, and still more preferably an alkylene group having 2 carbon atoms (i.e., ethylene group). In addition, when n is 2 or more, multiple R2 groups may be the same or different.
[0049] n is 1-50, preferably 1-30, more preferably 1-10.
[0050] In formula (1), * represents a bond, and * is preferably a bond that bonds to a phosphorus atom of a phosphate skeleton.
[0051] In the present invention, the phosphate ester is preferably a compound represented by the following formula (2) or formula (3), and more preferably a compound represented by formula (2). In addition, the phosphate ester in the present invention may be a mixture of compounds represented by formula (2) and formula (3).
[0052]
[0053] In formula (2) and formula (3), R1 and n have the same meanings as R1 and n in formula (1).
[0054] From the viewpoint of further suppressing whitening, the content of the phosphate ester in the resin layer is preferably 0.04 mass % or more, more preferably 0.1 mass % or more, and from the viewpoint of heat yellowing resistance, the content of the phosphate ester in the resin layer is preferably 0.5 mass % or less, more preferably 0.3 mass % or less.
[0055] [Polyvinyl acetal resin]
[0056] The resin layer of the present invention contains a polyvinyl acetal resin. By containing the polyvinyl acetal resin, the adhesion between the various members constituting the touch panel, such as the cover glass and the sensor glass, can be improved, and the impact absorption is improved, and cracks and breakages are less likely to occur.
[0057] The polyvinyl acetal resin can be obtained by acetalizing polyvinyl alcohol (PVA) with an aldehyde. That is, the polyvinyl acetal resin is preferably an acetalized product of polyvinyl alcohol (PVA). Polyvinyl alcohol (PVA) can be obtained by saponifying polyvinyl esters such as polyvinyl acetate, for example. The degree of saponification of polyvinyl alcohol is usually 70 to 99.9 mol%. The polyvinyl acetal resin can be used alone or in combination of two or more.
[0058] The average degree of polymerization of the polyvinyl acetal resin is preferably 200 or more, more preferably 500 or more, further preferably 1000 or more, and further preferably 1500 or more. The average degree of polymerization of the polyvinyl acetal resin is preferably 5000 or less, more preferably 4000 or less, and further preferably 3500 or less.
[0059] The average degree of polymerization of the polyvinyl acetal resin is the same as the average degree of polymerization of PVA which is a raw material of the polyvinyl acetal resin. The average degree of polymerization of PVA can be determined by a method in accordance with JIS K6726 "Testing methods for polyvinyl alcohol".
[0060] The aldehyde used for acetalization is not particularly limited, but an aldehyde having 1 to 10 carbon atoms is preferably used, an aldehyde having 3 to 5 carbon atoms is more preferably used, an aldehyde having 4 or 5 carbon atoms is further preferably used, and an aldehyde having 4 carbon atoms is particularly preferably used.
[0061] The aldehyde having 1 to 10 carbon atoms is not particularly limited, and examples thereof include formaldehyde, acetaldehyde, propionaldehyde, n-butylaldehyde, isobutylaldehyde, n-pentylaldehyde, 2-ethylbutylaldehyde, n-hexylaldehyde, n-octylaldehyde, n-nonylaldehyde, n-decylaldehyde, and benzaldehyde. Among them, acetaldehyde, propionaldehyde, n-butylaldehyde, isobutylaldehyde, n-hexylaldehyde, or n-pentylaldehyde is preferred, propionaldehyde, n-butylaldehyde, isobutylaldehyde, or n-pentylaldehyde is more preferred, n-butylaldehyde or n-pentylaldehyde is further preferred, and n-butylaldehyde is most preferred. The aldehydes may be used alone or in combination of two or more.
[0062] The number of carbon atoms in the acetal group contained in the polyvinyl acetal resin is not particularly limited, but is preferably 1 to 10, more preferably 3 to 5, further preferably 4 or 5, and particularly preferably 4. Specifically, the acetal group is particularly preferably a butyral group, and therefore, the polyvinyl acetal resin is preferably a polyvinyl butyral resin.
[0063] The hydroxyl amount of the polyvinyl acetal resin is preferably 15 mol% or more, and preferably 38 mol% or less. By making the hydroxyl amount 15 mol% or more, the adhesion is easily improved. In addition, by making the hydroxyl amount 38 mol% or less, the resin layer is prevented from becoming too hard. From the viewpoint of adhesion, the above-mentioned hydroxyl amount is more preferably 20 mol% or more, and more preferably 25 mol% or more. In addition, the above-mentioned hydroxyl amount is more preferably 35% or less, and more preferably 33 mol% or less.
[0064] When a polyvinyl butyral resin is used as the polyvinyl acetal resin, from the same viewpoint, the hydroxyl group amount is 15 mol% or more, preferably 38 mol% or less, more preferably 20 mol% or more, further preferably 25 mol% or more, more preferably 35 mol% or less, further preferably 33 mol% or less.
[0065] The hydroxyl content of the polyvinyl acetal resin is a value expressed as a percentage by dividing the molar fraction of the ethylene groups to which hydroxyl groups are bonded by the total ethylene groups in the main chain. The ethylene groups to which hydroxyl groups are bonded can be measured, for example, in accordance with JIS K6728 "Testing methods for polyvinyl butyral".
[0066] The degree of acetalization of the polyvinyl acetal resin is preferably 47 mol% or more, and preferably 85 mol% or less. The degree of acetalization is more preferably 55 mol% or more, and further preferably 60 mol% or more, and further preferably 80 mol% or less, and further preferably 75 mol% or less.
[0067] In addition, when the acetal group is a butyral group and the polyvinyl acetal resin is a polyvinyl butyral resin, the acetalization degree means the butyralization degree.
[0068] The above-mentioned degree of acetalization is a value obtained by subtracting the amount of ethylene groups bonded with hydroxyl groups and the amount of ethylene groups bonded with acetyl groups from the total amount of ethylene groups in the main chain and dividing the obtained value by the total amount of ethylene groups in the main chain to obtain a molar fraction expressed as a percentage. The degree of acetalization (degree of butyralization) can be calculated, for example, from the results measured by a method in accordance with JIS K6728 "Testing methods for polyvinyl butyral".
[0069] The degree of acetylation of the polyvinyl acetal resin is preferably 30 mol% or less, more preferably 20 mol% or less, further preferably 10 mol% or less, and further preferably 2 mol% or less. If the degree of acetylation is below the upper limit, the moisture resistance of the resin layer becomes high. In addition, the degree of acetylation is not particularly limited, but is preferably 0.01 mol% or more, and more preferably 0.1 mol% or more.
[0070] The acetylation degree is a value expressed as a percentage of the molar fraction obtained by dividing the amount of ethylene groups bonded with acetyl groups by the total amount of ethylene groups in the main chain. The amount of ethylene groups bonded with acetyl groups can be measured, for example, in accordance with JIS K6728 "Testing methods for polyvinyl butyral".
[0071] [Other resins]
[0072] The resin layer may contain resins other than the polyvinyl acetal resin within a range that does not hinder the effect of the present invention. As resins other than the polyvinyl acetal resin, for example, ethylene-vinyl acetate copolymer resins, ionomer resins, polyurethane resins, thermoplastic elastomers, acrylic resins, etc. can be cited. Based on the total amount of resins contained in the resin layer, the content of the polyvinyl acetal resin is preferably 50% by mass or more, more preferably 80% by mass or more, and further preferably 100% by mass.
[0073] [Plasticizer]
[0074] The resin layer of the present invention preferably contains a plasticizer. By including the plasticizer in the resin layer together with the polyvinyl acetal resin, the impact absorption can be further improved. In addition, the resin layer becomes softer due to the inclusion of the plasticizer and is easy to adjust to a predetermined shape.
[0075] As the plasticizer, for example, organic phosphorus plasticizers such as organic ester plasticizers, organic phosphate plasticizers and organic phosphite plasticizers, organic ether plasticizers such as polyalkylene glycol plasticizers and polyoxyalkylene ether plasticizers, alcohol plasticizers, etc. can be mentioned. One type of plasticizer can be used alone, or two or more types can be used in combination. Among the above, organic ester plasticizers and polyalkylene glycol plasticizers are preferred, and organic ester plasticizers are more preferred. As preferred organic ester plasticizers, monobasic organic acid esters and polybasic organic acid esters can be mentioned.
[0076] As monobasic organic acid esters, esters formed by diols and monobasic organic acids can be mentioned. As diols, polyalkylene glycols in which each alkylene unit has 2 to 4 carbon atoms (preferably 2 or 3 carbon atoms) and the number of repeating alkylene units is 2 to 10 (preferably 2 to 4). In addition, as diols, monoalkylene glycols (i.e., the number of repeating units is 1) in which the number of carbon atoms is 2 to 4, preferably 2 or 3 carbon atoms can also be mentioned.
[0077] Specific examples of the diol include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, tetrapropylene glycol, and butylene glycol.
[0078] Examples of the monobasic organic acid include organic acids having 3 to 10 carbon atoms, and specific examples thereof include butyric acid, isobutyric acid, hexanoic acid, 2-ethylbutyric acid, heptanoic acid, n-octanoic acid, 2-ethylhexanoic acid, n-nonanoic acid, and decanoic acid.
[0079] Specific examples of monobasic organic acid esters include triethylene glycol di-2-ethylbutyrate, triethylene glycol di-2-ethylhexanoate, triethylene glycol dioctanoate, triethylene glycol di-n-octanoate, triethylene glycol di-n-heptanoate, tetraethylene glycol di-n-heptanoate, tetraethylene glycol di-2-ethylhexanoate, diethylene glycol di-2-ethylbutyrate, diethylene glycol di-2-ethylhexanoate, dipropylene glycol di-2-ethylbutyrate, triethylene glycol di-2 -ethyl valerate, tetraethylene glycol di-2-ethyl butyrate, diethylene glycol dioctanoate, triethylene glycol di-n-heptanoate, tetraethylene glycol di-n-heptanoate, triethylene glycol di-2-ethyl butyrate, ethylene glycol di-2-ethyl butyrate, 1,2-propylene glycol di-2-ethyl butyrate, 1,3-propylene glycol di-2-ethyl butyrate, 1,4-butanediol di-2-ethyl butyrate, 1,2-butanediol di-2-ethyl butyrate, etc.
[0080] Examples of polybasic organic acid esters include ester compounds formed by dibasic organic acids having 4 to 12 carbon atoms, such as adipic acid, sebacic acid, azelaic acid, and phthalic acid, and alcohols having 4 to 10 carbon atoms. The alcohols having 4 to 10 carbon atoms may have a linear, branched, or cyclic structure.
[0081] Specifically, dibutyl sebacate, dioctyl azelate, dihexyl adipate, dioctyl adipate, hexylcyclohexyl adipate, hexylcyclohexyl adipate, diisononyl adipate, heptylnonyl adipate, dibutyl carbitol adipate, mixed adipate, dioctyl phthalate, dibutyl phthalate, etc. can be mentioned. In addition, oil-modified sebacic acid alkyd resins, etc. can also be mentioned. As mixed adipate, adipate made from two or more alcohols selected from alkyl alcohols having 4 to 9 carbon atoms and cyclic alcohols having 4 to 9 carbon atoms can be mentioned.
[0082] The organic ester plasticizer is not limited to the complete ester of the above esters, and may be a partial ester. For example, it may be a partial ester formed by a glycol and a monobasic organic acid, or it may be a partial ester formed by a dibasic organic acid and an alcohol. Specifically, triethylene glycol-mono-2-ethylhexanoate and the like may be cited.
[0083] In addition, partial esters of trivalent or higher alcohols such as glycerol and monovalent organic acids may be used. Examples of the monovalent organic acid include monovalent organic acids having 3 to 24 carbon atoms, preferably 6 to 18 carbon atoms. Specific examples of partial esters of trivalent or higher alcohols and monovalent organic acids include monoesters or diesters of glycerol and stearic acid, and monoesters or diesters of glycerol and 2-ethylhexanoic acid.
[0084] As the organic ester plasticizer, among the above, triethylene glycol di-2-ethylhexanoate (3GO) and dioctyl adipate (DOA) are particularly preferably used.
[0085] Examples of the organic phosphorus plasticizer include phosphoric acid esters such as tributoxyethyl phosphate, isodecyl diphenyl phosphate, and triisopropyl phosphate.
[0086] Examples of the polyalkylene glycol plasticizer include polyethylene glycol, polypropylene glycol, poly(ethylene oxide / propylene oxide) block copolymers, poly(ethylene oxide / propylene oxide) random copolymers, and polybutylene glycol. Among these, polypropylene glycol is preferred.
[0087] The polyoxyalkylene ether plasticizer is an ether compound formed by a monohydric or polyhydric alcohol and a polyoxyalkylene group.
[0088] Specific examples of the polyoxyalkylene ether plasticizer include polyoxyethylene hexyl ether, polyoxyethylene heptyl ether, polyoxyethylene octyl ether, polyoxyethylene-2-ethylhexyl ether, polyoxyethylene nonyl ether, polyoxyethylene decyl ether, polyoxyethylene allyl ether, polyoxypropylene allyl ether, polyoxyethylene glyceryl ether, polyoxypropylene glyceryl ether, polyoxyethylene diglyceryl ether, polyoxypropylene diglyceryl ether, polyoxyalkylene pentaerythritol ether, and polycaprolactone triol.
[0089] The polyoxyalkylene ether plasticizer is preferably an ether compound of a polyhydric alcohol and a polyoxyalkylene group, more preferably an ether compound of glycerol or diglycerol and a polyoxyalkylene group, and still more preferably an ether compound of glycerol or diglycerol and a polyoxypropylene group.
[0090] As alcohol plasticizers, alcohols other than polyalkylene glycol plasticizers and polyoxyalkylene ether plasticizers can be cited. Specifically, various polyols such as ethylene glycol, propylene glycol, butylene glycol, hexylene glycol, trimethylolpropane, pentaerythritol, glycerol, and diglycerol can be cited. Among them, ethylene glycol is preferred.
[0091] Preferably, the content of the plasticizer in the resin layer is preferably 5 parts by mass or more, more preferably 15 parts by mass or more, further preferably 30 parts by mass or more, relative to 100 parts by mass of the polyacetal resin, and is preferably 100 parts by mass or less, more preferably 60 parts by mass or less, further preferably 50 parts by mass or less.
[0092] [Other additives]
[0093] The resin layer of the present invention may contain known additives such as tackifier resin, adhesion regulator, emulsifier, softener, fine particles, filler, pigment, dye, silane coupling agent, antioxidant, surfactant, wax, etc. as needed.
[0094] (Film shape)
[0095] From the viewpoint of being able to be easily attached to a substrate, the interlayer adhesive of the present invention is preferably in the form of a film. In this case, the interlayer adhesive of the present invention can be obtained, for example, by mixing a resin, a phosphate ester, and various additives as required, and molding the obtained resin composition by extrusion molding, pressure molding, etc.
[0096] [thickness]
[0097] The thickness of the interlayer adhesive of the present invention is not particularly limited and can be appropriately adjusted according to the size and type of the touch panel used. The thickness of the interlayer adhesive is preferably 0.05 mm or more, more preferably 0.1 mm or more, and further preferably 0.15 mm or more, and preferably 5 mm or less, more preferably 3 mm or less, and further preferably 1 mm or less.
[0098] [Touch panel]
[0099] The interlayer adhesive of the present invention can be suitably used for bonding the members constituting a touch panel. In addition, the present invention can provide a touch panel comprising the interlayer adhesive.
[0100] Furthermore, an interlayer adhesive for a touch panel using such an interlayer adhesive of the present invention is also one of the present invention.
[0101] Figure 1 One embodiment of the touch panel of the present invention is shown in FIG. It should be noted that the present invention is not limited to the contents of the drawings.
[0102] Figure 1 The touch panel 10 shown in the figure has a cover glass 11, a sensor glass 12 and a liquid crystal panel 13 in sequence. The cover glass 11 is a light-transmitting member, and its surface becomes an operation surface that is contacted by the user's finger or the like during a touch operation. The sensor glass 12 has an ITO pattern (not shown) formed on its surface, thereby being able to detect a touch operation performed by the user's finger (detection object). It should be noted that the sensor glass 12 can be a single-layer structure or a multi-layer structure. In addition, the liquid crystal panel 13 can be used to display a specified image. It should be noted that an organic EL panel can also be used instead of the liquid crystal panel 13.
[0103] The interlayer adhesive 14 of the present invention is provided between the cover glass 11 and the sensor glass 12, and the cover glass 11 and the sensor glass 12 are bonded and fixed. Since polyvinyl acetal resin is used in the interlayer adhesive 14, the adhesion between the cover glass 11 and the sensor glass 12 is good, and the impact absorption is improved, and cracks and breakages are not easily generated.
[0104] Furthermore, since the resin layer constituting the interlayer adhesive 14 contains phosphate ester, whitening can be suppressed even when the temperature and humidity are high under the operating conditions of the touch panel (when voltage is applied).
[0105] In addition, if Figure 1 As shown, the interlayer adhesive 14 of the present invention may be used between the sensor glass 12 and the liquid crystal panel 13 as necessary, but a commonly used optical adhesive (OCA) or the like may also be used.
[0106] It should be noted that Figure 1 Although the touch panel including the cover glass 11 , the sensor glass 12 , the liquid crystal panel 13 , and the interlayer adhesive 14 is shown in the figure, the touch panel may also include other structures.
[0107] In addition, if Figure 2 As shown, the touch panel 2 may include a touch panel body 100 and a cover member 151 .
[0108] The cover member 151 includes a first member 61 made of a glass plate, an interlayer adhesive 65, and a second member 160. The interlayer adhesive 65 is arranged on the second surface 61B with a substantially uniform thickness. The second member 160 is arranged in a manner of being in close contact with the interlayer adhesive 65 along the outer surface of the interlayer adhesive 65. The second member 160 is arranged in a manner of following the outer surface of the interlayer adhesive 65.
[0109] The first member 61 has a first surface 61A and a second surface 61B opposite to the first surface 61A. The so-called operation surface is the first surface 61A. A transparent interlayer adhesive 65 is disposed on the entire surface of the second surface 61B.
[0110] The material of the first member 61 is, for example, a glass plate, or a thin plate glass having flexibility. As the first member 61, from the viewpoint of lightness, a glass plate having a thickness of 0.01 mm or more and 0.55 mm or less is preferably used. When the cover member 151 having a size of 25 inches or more is constructed, a glass plate having a thickness of 0.01 mm or more and 1.85 mm or less is preferably used.
[0111] In addition, if a glass plate with a thickness of 0.7 mm or less is used, a thinner cover member 151 can be formed. In the cover member 151 corresponding to the touch panel body 100 with a large screen size of 25 inches or more, in order to prevent a large amount of deflection, it is desirable to use a thicker glass plate as the first member 61, but from the perspective of the overall thickness, the thickness of the first member 61 is preferably 2.5 mm or less.
[0112] The material of the second member 160 is, for example, a glass plate, or a thin plate glass having flexibility. From the viewpoint of light weight, it is preferred to use a glass plate with a thickness of 0.01 mm or more and 0.55 mm or less as the second member 160. When the cover member 151 is formed to have a size of 25 inches or more, it is preferred to use a glass plate with a thickness of 0.01 mm or more and 1.85 mm or less. If it is a glass plate of this thickness, it can be easily configured as the second member 160 in a manner that follows the outer surface of the interlayer adhesive 65, and it can also suppress the mixing of bubbles and the like.
[0113] The cover member 151 is configured by arranging a first member 61 made of a glass plate and a second member 160 made of a glass plate with an interlayer adhesive 65 interposed therebetween.
[0114] The touch panel body 100 is mounted on the outer surface of the second member 160. Figure 2In the figure, a touch panel body 100 having a structure of two laminated substrates is illustrated. To briefly explain the touch panel body 100, the touch panel body 100 has a first substrate 111 and a second substrate 112. The first substrate 111 and the second substrate 112 are transparent, for example, made of a resin film or a glass plate. A transmitting electrode of a sensor electrode is arranged on the first substrate 111, and a receiving electrode of a sensor electrode is arranged on the second substrate 112. The first substrate 111 and the second substrate 112 are bonded together using a transparent adhesive 115. In addition, a transparent adhesive 116 used when bonding to the cover member 151 is provided on the second substrate 112. The touch panel body 100 is mounted on the outer surface of the second member 160 via the adhesive 116. The adhesive 115 and the adhesive 116 can use the interlayer adhesive according to the present invention, but a commonly used optical adhesive (OCA) or the like can also be used.
[0115] The manufacturing method of the touch panel of the present invention is not particularly limited, but it is preferably manufactured by vacuum packaging. For example, an interlayer adhesive is introduced into a part or all of the components constituting the touch panel, placed in a vacuum package, and after decompression and suction, pre-bonding is performed at about 70 to 110° C. to obtain a laminate. Next, the laminate is placed in an autoclave or pressurized, and crimped at about 120 to 150° C. and a pressure of 1 to 1.5 MPa. By operating as described above, a touch panel can be obtained. Example
[0116] The present invention will be described in more detail using examples, but the present invention is not limited to these examples.
[0117] In addition, the measurement and evaluation of various physical properties were performed as follows.
[0118] [Whitening distance obtained from the heat and humidity resistance test]
[0119] The cover glass laminates prepared in each example and comparative example were maintained at a temperature of 60°C and a relative humidity of 90% while applying a voltage (5V) using a function generator, and the whitening distance after 1000 hours was measured. The whitening distance was obtained by measuring the distance from the edge of the cover glass laminate to the whitened portion, and was evaluated according to the following criteria.
[0120] (Evaluation Criteria)
[0121] A: Whitening distance is less than 3mm
[0122] B: Whitening distance is greater than 3mm and less than 5mm
[0123] C: Whitening distance greater than 5mm
[0124] The plasticizers and phosphate esters used in Examples and Comparative Examples are as follows.
[0125] <Plasticizer>
[0126] 3GO: Triethylene glycol di-2-ethylhexanoate
[0127] <Phosphate ester>
[0128] "Platinum A208B" manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd., a compound wherein R1 is dodecyl and n is 2 in formula (2). HLB=8.
[0129] "DISPERBYK-102" manufactured by Bic Chemie Co., Ltd. is a phosphoric acid ester having a polyoxyalkylene alkyl ether group.
[0130] [Example 1]
[0131] (Manufacture of polyvinyl butyral resin)
[0132] 1800g of ion exchange water and 200g of polyvinyl alcohol A (average degree of polymerization of 1700, degree of saponification of 99 mol%) were added to a reactor equipped with a stirring device, and heated and dissolved while stirring to obtain a polyvinyl alcohol solution. Next, 25% hydrochloric acid as a catalyst was added to the solution to make the hydrochloric acid concentration 0.2% by weight, and after adjusting the temperature to 15°C, 16g of n-butyl aldehyde was added while stirring. Thereafter, 95g of n-butyl aldehyde was added, and as a result, polyvinyl alcohol butyral resin in the form of white particles was precipitated. Ten minutes after precipitation, 25% hydrochloric acid was added to make it 1.8% by weight, and heated to 63°C and maintained for 2 hours. Then, the solution was cooled, washed with excess water, rinsed with unreacted butyl aldehyde, and the hydrochloric acid catalyst was neutralized with sodium bicarbonate as a general neutralizing agent, and further washed with excess water and dried to obtain polyvinyl alcohol butyral resin. The obtained polyvinyl butyral resin had a hydroxyl group content of 30.6 mol %, an acetalization degree of 68.7 mol %, and an acetylation degree of 0.7 mol %.
[0133] (Manufacturing of interlayer adhesive)
[0134] 100 parts by mass of the polyvinyl butyral resin, 35 parts by mass of 3GO as a plasticizer, and 0.14 parts by mass of Primer A208B as a phosphate ester were mixed, fully melt-kneaded using a roll mixer, and then press-molded at 150° C. for 10 minutes using a press molding machine to obtain an interlayer adhesive with a thickness of 0.4 mm.
[0135] (evaluate)
[0136] Cover glass (soda-lime glass manufactured by Nippon Sheet Glass Co., Ltd.) and sensor glass on which an ITO pattern was formed (manufactured by Technoprene Co., Ltd., ITO thickness: 150 nm, resistance value: approximately 10Ω / □) were prepared.
[0137] The interlayer adhesive prepared as described above was sandwiched between the sensor glass and the cover glass to obtain a laminate. The laminate was placed in a rubber bag, degassed at a vacuum of 1.0 MPa for 10 minutes, and then moved into an oven at a temperature of 100° C. in a degassed state, and the laminate was further temporarily pressed until it reached 85° C. The temporarily pressed laminate was pressed for 20 minutes in an autoclave at 140° C. and a pressure of 1.3 MPa to obtain a cover glass laminate in which the cover glass, the resin layer (interlayer adhesive), and the sensor glass were sequentially stacked.
[0138] The whitening distance of the cover glass laminate was measured as described above. The results are shown in Table 1.
[0139] [Example 2]
[0140] In the production of the interlayer adhesive of Example 1, the same procedures as in Example 1 were carried out except that the amount of Primer A208B was changed to 2 equivalents (0.28 parts by mass).
[0141] [Example 3]
[0142] In the production of the interlayer adhesive of Example 1, the same procedures as in Example 1 were carried out except that the amount of Primer A208B was changed to 4 / 10 equivalent (0.056 parts by mass).
[0143] [Example 4]
[0144] In the production of the interlayer adhesive of Example 1, the same procedures as in Example 1 were carried out except that the type of phosphate ester was changed from Primer A208B to DISPERBYK-102.
[0145] [Comparative Example 1]
[0146] In the production of the interlayer adhesive of Example 1, the same procedure as in Example 1 was carried out except that the phosphoric acid ester was not added.
[0147] [Table 1]
[0148] Table 1
[0149]
[0150] ※ The PVB and plasticizer in Table 1 are expressed in parts by mass. The content of phosphate ester is expressed in mass % in the resin layer.
[0151] As described above, by using the interlayer adhesive of each example containing a phosphoric acid ester, it is possible to suppress the whitening of the touch panel in the moisture and heat resistance test.
[0152] On the other hand, the interlayer adhesive of each comparative example does not contain a phosphate ester and cannot suppress the whitening of the touch panel in the moisture and heat resistance test.
[0153] Description of Reference Numerals
[0154] 2.10 Touch Panel
[0155] 11 Cover glass
[0156] 12 Sensor glass
[0157] 13 LCD Panel
[0158] 14 Interlayer adhesive
[0159] 61 First Component
[0160] 65 interlayer adhesive
[0161] 100 Touch panel body
[0162] 111 First Substrate
[0163] 112 Second substrate
[0164] 115, 116 Adhesives
[0165] 151 Cover component
[0166] 160 Second Component
Claims
1. An interlayer adhesive comprising a resin layer comprising a polyvinyl acetal resin, wherein the resin layer contains a phosphoric acid ester. 2 . The interlayer adhesive according to claim 1 , wherein a concentration of the phosphoric acid ester in the resin layer is 0.1% by mass or more. 3 . The interlayer adhesive according to claim 2 , wherein a concentration of the phosphoric acid ester in the resin layer is 0.5 mass % or less. The interlayer adhesive according to any one of claims 1 to 3, wherein the HLB of the phosphoric acid ester is 10 or less. 5 . The interlayer adhesive according to claim 1 , wherein the phosphoric acid ester has a polyoxyalkylene alkyl ether group.
6. The interlayer adhesive according to claim 5, wherein the polyoxyalkylene alkyl ether group is a compound represented by formula (1): R1 is an alkyl group having 8 to 18 carbon atoms, R2 is an alkylene group having 2 to 6 carbon atoms, n is 1 to 10, and * represents a connecting bond.
7. The interlayer adhesive according to any one of claims 1 to 6, wherein the phosphate ester is a compound represented by formula (2) or formula (3), In formula (2) and formula (3), R1 is an alkyl group having 8 to 18 carbon atoms, and n is 1 to 10. 8 . The interlayer adhesive according to claim 1 , wherein the phosphate ester has a dodecyl group. 9 . The interlayer adhesive according to claim 1 , wherein the polyvinyl acetal resin is a polyvinyl butyral resin. 10 . The interlayer adhesive according to claim 1 , wherein the resin layer contains a plasticizer. 11 . An interlayer adhesive for a touch panel, comprising the interlayer adhesive according to claim 1 . 12 . A touch panel comprising the interlayer adhesive according to claim 1 .
Citation Information
Patent Citations
Interlayer filling material for touch panels, and touch panel laminate
WO2016186029A1